2013
DOI: 10.1038/bjc.2013.650
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and outcome of young breast cancer patients in the United Kingdom: the POSH study

Abstract: Background:Black ethnic groups have a higher breast cancer mortality than Whites. American studies have identified variations in tumour biology and unequal health-care access as causative factors. We compared tumour pathology, treatment and outcomes in three ethnic groups in young breast cancer patients treated in the United Kingdom.Methods:Women aged ⩽40 years at breast cancer diagnosis were recruited to the POSH national cohort study (MREC: 00/06/69). Personal characteristics, tumour pathology and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 43 publications
2
65
1
Order By: Relevance
“…In our study 12% of the patients had metastatic disease at the time of diagnosis. This is higher than it is reported in the POSH study (2.5%) where women aged ≤40 years were recruited (Copson et al, 2014).Our finding is similar with another study from Turkey; Uyetürk et al reported that 12.6% of breast cancer patients were presented with stage IV disease. There was no difference between stage IV and other stages in terms of age at diagnosis (Uyeturk et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…In our study 12% of the patients had metastatic disease at the time of diagnosis. This is higher than it is reported in the POSH study (2.5%) where women aged ≤40 years were recruited (Copson et al, 2014).Our finding is similar with another study from Turkey; Uyetürk et al reported that 12.6% of breast cancer patients were presented with stage IV disease. There was no difference between stage IV and other stages in terms of age at diagnosis (Uyeturk et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…There is limited, predominantly epidemiological, data on ethnic breast cancer within the UK population that points to similar variation in the biology and outcome of the disease across different backgrounds [21, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…11 In the UK, 5-year distant breast cancer relapse-free survival is 62·8% for young black women, compared with 77% for young white women with equal access to health care (p=0·0053). 12 Racial disparities in breast cancer survival between and within countries are linked to the availability of early detection, access to diagnosis and treatment, cultural differences in lifestyle behaviours, socioeconomic factors, and differences in the biological characteristics of breast cancer. 13 …”
Section: Introductionmentioning
confidence: 99%